2013
DOI: 10.7567/jjap.52.09kc04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sn2+ Ion Size on Sn Doped SrTiO3

Abstract: We discuss the doping effect of Sn2+ on ATiO3 perovskites by comparing with those of Pb and Ba. The solution energy of Sn into A sites of ATiO3 perovskites shows minimum when the lattice size is almost the same as that of SrTiO3 (STO), as determined by first-principles calculations. In dielectric measurements of these STO-based ceramics, the Sn2+-doped STO ceramics showed a higher peak temperature than the Pb2+- or Ba2+-doped STO ceramics at the same doping amount. In addition, the maximum polarization obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
8
0
5
Order By: Relevance
“…Previous work by Suzuki et al reported substitution of Sn 2+ on both the A and B sites of SrTiO 3 . 8,9 Refinements that modeled this two-site substitution were attempted, but the additional refined occupancies were unstable and the refined model inconclusive. In addition to Sn-substitution on A-site occupancies were determined using the diffraction data collected on the NOMAD diffractometer (wider Q-range of data) and applied to these refinements.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work by Suzuki et al reported substitution of Sn 2+ on both the A and B sites of SrTiO 3 . 8,9 Refinements that modeled this two-site substitution were attempted, but the additional refined occupancies were unstable and the refined model inconclusive. In addition to Sn-substitution on A-site occupancies were determined using the diffraction data collected on the NOMAD diffractometer (wider Q-range of data) and applied to these refinements.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 However, off-centering of an ion in a mixed (alloy) site cannot be refined against Bragg-scattering data, and indeed, this was found to be true insofar as any attempt to do this yielded unstable refinements. Sn 2+ off-centering is supported from a perspective of bond valence sums (BVS), with an Sn 2+ BVS of 1.16 in the 1a Wyckoff site of P m3m.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations